Transformational Leadership in Driving Change in Madrasahs: A Comparative Study of Public and Private Madrasah Principals - Eci Sriwahyuni; Usdarisman Usdarisman; Emi Fikrah (GHAITSA : Islamic Education Journal, 2026)
Using MTsN 17 Tanah Datar and MTsS Balimbing Tanah Datar as case studies, this study attempts to examine and contrast how madrasah principals apply transformational leadership in promoting organizational change inside public and private madrasahs. The study uses a multiple case study design and a qualitative methodology, gathering data through documentation, in-depth interviews, and observation. Data analysis follows the Miles and Huberman approach, consisting of data reduction, data display, and conclusion formulation. The results show that both principals effectively implemented the four fundamental elements of transformational leadership: idealized influence, intellectual stimulation, inspirational drive, and customized consideration as suggested by Bass and Avolio (1994). The principal of MTsN 17 Tanah Datar exhibits a disciplined, professional, and innovative leadership style that incorporates transformational, instructional, and distributed leadership techniques, focused on academic quality enhancement and managerial efficiency. Meanwhile, the principle of MTsS Balimbing Tanah Datar promotes emotional, spiritual, and participatory qualities founded on Islamic values and Minangkabau indigenous wisdom. These results demonstrate that a contextual, flexible, and long-lasting model of Islamic educational leadership is produced when a leader successfully integrates universal transformational values with spirituality and local culture.